Density and specific gravity of Kelat (Syzygium spp.) according to different height levels / Shamsul Anuar Mohamad Kasim - Mohamad Kasim, Shamsul Anuar (2004)
The study of density and specific gravity was performed on Kelat wood (Syzygium spp.). Specific gravity was determined using the maximum moisture content method and density is known as slugs per cubic meter. The samples were analyzed from three levels of a tree - base, middle and top. The result indicated that density was highest at base and lowest at the middle portion. On the other hand, specific gravity decreased from base to middle portion and then top portion. Thus specific gravity is inversely related to different height levels.